The presumption of rank in examples of the poetry of Antarah bin Shaddad (Latakia University Journal - Arts and Humanities Sciences Series, 2022)
The rank constitutes a verbal predicate that has its relations that are present in the poetic context, and it has an important role in the performance of the meaning. It has emerged in the poetry of Antarah bin Shaddad from several aspects, so he had a bridge to cross to the realization of the meaning. And the substitution, and the rank of the genitive, the rank of distinction, the rank of transcribers, the rank between the affirmative and the categorical, the rank of letters of all kinds, the rank of the excluded, the rank of the attribution between the subject and the predicate, the verb and its subject.          It can be said that the presumption of rank in Antara's poetry was not absurd, but was appropriate in its places, enriched his hair, and gave him a special aesthetic.